Microsoft HoloLens by example : create immersive augmented reality experiences - Newnham, Joshua (Packt Publishing, 2017)
Get to grips with HoloLens development as you create mixed reality apps from scratchAbout This BookCreate awesome Augmented Reality (AR) apps for the Microsoft HoloLens platformUnleash the power of Unity SDK for HoloLens to create next generation AR appsExplore the exciting world of gesture control, visual mapping, voice command for apps, and many more cutting edge possibilities with HoloLensWho This Book Is ForThis book is for developers who have some experience with programming in any of the major languages such as C#, C++, and so on. You do need any knowledge of Augmented Reality development. What You Will LearnExtend the computing experience beyond the flat glass screen by placing and embedding virtual objects holograms) into the physical worldInteract with the holograms using gaze, gestures, and voiceEnhance the experience with spatial soundAllow multiple users to naturally collaborate with each otherIntegrate voice commands into your own HoloLens projectsExperiment with techniques to better understand the real worldImplement a user interface in Mixed RealityBlend the virtual and physical world by making the holograms interact and react to the physical environmentIn DetailAre you a developer who is fascinated with Microsoft HoloLens and its capabilities? Do you want to learn the intricacies of working with the HoloLens SDK and create your own apps? If so, this is the book for you. This book introduces and demystifies the HoloLens platform and introduces new ways you can interact with computers (Mixed Reality). It will teach you the important concepts, get you excited about the possibilities, and give you the tools to continue exploring and experimenting. You will go through the journey of creating four independent examples throughout the book, two using DirectX and two using Unity. You will learn to implement spatial mapping and gesture control, incorporate spatial sound, and work with different types of input and gaze. You will also learn to use the Unity 5 SDK for HoloLens and create apps with it. Collectively, the apps explore the major concepts of HoloLens, but each app is independent, giving you the flexibility to choose where to start (and end). Style and approachThis book takes an example-based approach where you'll build AR apps with increasing difficulty. You will learn more about HoloLens platform as well as AR app development in general.